An enigmatic beetle with affinity to Lamingtoniidae in mid-Cretaceous amber from northern Myanmar (Coleoptera: Cucujoidea) - Li, Yan-Da; Leschen, Richard A. B.; Liu, Zhen-Hua; Huang, Di-Ying; Cai, Chen-Yang (Frontiers in Ecology and Evolution, 2022)
An enigmatic cucujiform beetle, Alloterocucus atratus Li, Leschen, Liu & Cai gen. et sp. nov., is reported from mid-Cretaceous Burmese amber. The character combination of the new fossil is not completely accordant with any of the known cucujoid or erotyloid families. Based on our phylogenetic analyses, Alloterocucus is assigned to Cucujoidea and may be allied to Lamingtoniidae, which contains a single Australasian genus in the extant fauna. Alloterocucus shares with Lamingtoniidae a similar habitus and a series of characters, including the absence of postocular constriction, 3-segmented antennal club, externally open procoxal cavities, laterally open mesocoxal cavities, exposed pro- and mesotrochantins, and the absence of epipleural fovea and pronotal setose cavities, but differs from extant Lamingtoniidae in its apically truncate terminal maxillary palpomeres, 5-5-4 tarsi in male and absence of distinct dorsal punctation.